America's Pragmatic Role?. Issue 3 (26th September 2020) - Avant, Deborah
Abstract: What has made the United States a global leader? Though analysts often attribute American success to a combination of resources and ideas, a subtle undercurrent in these arguments points to pragmatism and the creativity it often generates as an important part of the story. First theorized by American philosophers in the nineteenth and early twentieth centuries, pragmatism emphasizes that creativity can reshape how we see norms and interests to make cooperation more likely. After discussing the basic elements of pragmatism and its intersection with prominent international relations arguments, I show how the creativity that pragmatism envisions appears in each of these books. Though the collected authors do not label themselves as pragmatists, piecing these pragmatic elements together demonstrates the importance of creativity for key global leadership moments in the twentieth century, as well as important, if under-appreciated, governance innovations in the twenty-first century. It also offers insights into how the United States might move into the future.